PENGARUH TAHU SUSU DENGAN KONSENTRASI ASAM CUKA DAN PENAMBAHAN SUSU SAPI (Fresh Milk) - wulandari, anita; Cahyani, Wahyu Kanti Dwi (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
Soybean is generally used as a raw material for making tofu. Milk is a food ingredient, which contains all the nutrients needed by the body. One of the products that can be made with this milk ingredient is Milk Tofu. Vinegar/acetic acid is an organic compound containing a carboxylic acid group, which is known as a sour taste and aroma in food. The research method used was the experimental method, the experimental design used in this study was a completely randomized design (CRD) with one factor, namely the concentration of vinegar and the addition of milk with treatment P1 (20% + 1 liter of milk), P2 (25% vinegar +2 liters of milk), P3 (vinegar 30% + 3 liters of milk) with 3 treatments and repeated 3 times. Parameters observed were curd yield, texture and taste. If there is an effect then proceed with the DMRT test at a level of 5%. The results of the research on the highest curd yield were P2 (25% vinegar + 2 liters of milk) with a value of 1.94%. Meanwhile, preference for taste and texture was at P3 (30% vinegar + 3 liters of milk) with a value of 7, and for texture the highest score was at 6.83. While the best determination in research on vinegar treatment is 25%. In conclusion, the effect of this addition is influenced by the amount of vinegar and milk so that it can produce the texture and taste of curd.